Efeito gastroprotetor do monoterpeno (-)-carveol em modelos animais - Serafim, Catarina Alves de Lima (2021)
(-)-carveol (p-mentha-6,8-dien-2-ol) is a monocyclic monoterpenic alcohol, found in essential oils of vegetable species such as cumin (Carum carvi), orange (Citrus reticulata), currant and black tea. Pharmacological studies show that (-)-carveol has antitumor, antimicrobial, neuroprotective, antioxidant and anti-inflammatory activity. However, there are no studies in the literature on its gastroprotective activity, motivating the choice of this substance to conduct this study. Thus, the objective of this study was to verify the acute non-clinical toxicity and the gastroprotective effect of pre-treatment with (-)-carveol in animal models. To achieve this goal, a behavioral assessment was performed, an estimated 50% lethal dose (LD50), analysis of the gastroprotective effect with different models of acute induction by harmful agents (ethanol, stress, NSAIDs and pyloric ligation) and the mechanisms involved effect (antisecretory, cytoprotective, antioxidant and immunomodulators). The results obtained suggest that (-)-carveol has low toxicity, with an LD50 equal to or greater than 2.500 mg/kg according to OECD guide nº 423. In the ethanol-induced ulcer protocol, (-)-carveol (25, 50, 100 and 200 mg/kg, p.o) showed a gastroprotective effect with 46%, 70%, 91% and 93%, respectively, of injury inhibition ulcerative compared to the negative control group (tween 80 5%). In addition, (-)-carveol (100 mg/kg) restored the evaluated histological parameters. In injuries induced by stress due to contention and cold, (-)-carveol (25, 50, 100 and 200 mg/kg, p.o) reduced the ulcerative injury rate (ILU) by 18%, 43%, 61% and 62 %, respectively, compared to the negative control. In induction with NSAIDs (piroxicam), (-)-carveol (25, 50, 100 and 200 mg/kg, p.o) reduced the ILU by 14%, 30%, 59% and 60%, respectively, when compared to the control negative. In the experimental pylorus ligation protocol (containment of gastric juice), (- )-carveol (100 mg/kg) reduced the ILU in both routes of administration (oral and intraduodenal), did not change the pH and [H +], but decreased the volume of gastric secretion. Prior administration of N-Ethmalemaleimide blockers (NEM - sulfhydryl group blocker), Nω-Nitro-L-arginine methyl ester (L-NAME - NO synthesis inhibitor), glibenclamide (ATP-dependent potassium channel blocker - KATP) and indomethacin (cyclooxygenase inhibitor), significantly reduced the gastroprotection exerted by (-)-carveol, being able to infer the participation of these pathways in its gastroprotective activity. (-)-carveol also increased gastric mucus in the stomach tissue and showed antioxidant effects by increasing the concentration of reduced glutathione (GSH) and the activity of superoxide dismutase (SOD) and reducing the levels of malondialdehyde (MDA) and the activity of myeloperoxidase (MPO), but also demonstrated an immunomodulatory effect by reducing the inflammatory cytokines interleukin 1 beta (IL-1β) and the tumor necrosis factor alpha (TNF-α) and maintaining the basal levels of the anti-inflammatory cytokine interleukin 10 (IL-10).